(untitled) (AmeriQuests, 2017)
This paper addresses the historical development and current context of the United States’ obligation to Syrian refugees. Part I discusses the historical context of the domestic approach to accepting refugees and displaced persons. Part II addresses the role of domestic courts in enforcing international obligations to accept refugees. Part III reflects additional obstacles facing Syrians who seek legal protection in the United States. Part IV provides commentary on an alternative to admission, Syrian safe zones.